East African agriculture and climate change: A comprehensive analysis - Democratic Republic of the Congo - Nsombo, Blandine M.; Thomas, Timothy S.; Kyotalimye, Miriam; Waithaka, Michael (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Democratic Republic of the Congo that will appear in the peer-reviewed IFPRI monograph, East African Agriculture and Climate Change: A Comprehensive Analysis.